Improving Teacher Performance in Classroom Learning Through Periodic Collaborative Educational Supervision - Sulhawati Sulhawati (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to describe the steps of collaborative educational supervision periodically in carrying out learning. This research was conducted at SD Negeri 10 Belida Darat, Belida Darat District, Muara Enim Regency in the 2020/2021 academic year. This research is an action research, so this research is carried out in cycles. The implementation is for two cycles.The data that has been collected was analyzed using qualitative and quantitative analysis. In the first cycle, it concluded that there were four teachers with a percentage of 66.4%. There are still many teachers who have not concluded the lesson. This happens because the time is spent working on student worksheets only. For this reason, it is necessary to adjust the questions that are worked on in the student worksheets. Concluding the learning amounted to 6 teachers with a percentage of 100%. After the first cycle was carried out, then the teacher and researcher discussed how to conclude the learning turned out to bring satisfactory results. In the second cycle, the completeness of teacher development in groups has been achieved with satisfactory results.